Study on antioxidant activities and total phenolic compound of syzygium chlorantha and hopea odorata - Shiyamala Devi Sivakumar (2014)
The aim of the present study is to determine the total phenolic content and antioxidant activity of two hardwood species of selected Malaysian timber, namely Merawan (Hopeaodorata) and Kelat (Syzygium chlorantha).Not many studies on antioxidant activity and total phenolic content have been conducted with the species selected. Therefore, this study was also carried out in order to determine the relationship between the total phenolic content and the antioxidant activity of the selected species. Heartwood, sapwood, and bark of Merawan and Kelat were extracted with methanol using Soxhlet Extraction.The extracts were evaluated for antioxidant activity using 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. The total phenol content (TPC) of the extracts were determined by the Folin-Ciocalteu method and expressed as gallic acid equivalent (GAE). The present study showed that the sapwood of Merawan had the highest TPC followed by Merawan sapwood and Kelat heartwood. All wood extracts showed good antioxidant activities however the heartwood extracts of both species exhibited the strongest antioxidant activity. The lowest EC5„values based on the DPPH radical scavenging activity were shown by Merawan heartwood extracts as compared to the other samples. The correlation between TPC and the antioxidant absorbance based on the DPPH radical scavenging activity assay were positive. Relatively, the present results suggest that of the two hardwood species tested, Merawan (Hopea odorata) has the highest antioxidant activity and the highest total phenol content and have shown potential candidate to be used as sources of natural antioxidants.